2006
DOI: 10.1007/s00213-006-0402-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of midazolam on explicit vs implicit memory in a pediatric surgery setting

Abstract: Overall, it appears that midazolam induces a dissociation between explicit and implicit memory in young children in the pediatric surgery setting. Theoretical and clinical implications of the findings are discussed along with directions for future research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 35 publications
0
24
0
1
Order By: Relevance
“…Drugs currently used in clinical practice are reported in the following studies: midazolam was investigated in 33 trials [7, 1416, 19, 27, 28, 31, 33, 35, 39–45, 47, 48, 5054, 59, 61, 63, 66–71], nitrous oxide in seven [26, 30, 34, 42, 46, 50, 51], ketamine in eight [13–17, 26, 34, 37, 44, 49, 70], dexmedetomidine in one [49] and propofol in four [13, 14, 46, 47]. Besides, all drugs investigated in 23 studies were the ones currently used: 19 involved midazolam [7, 19, 27, 31, 33, 35, 40, 41, 5052, 54, 61, 63, 66–70], three nitrous oxide [46, 50, 51], four ketamine [13, 17, 49, 70], one dexmedetomidine [49] and two propofol [13,46]. …”
Section: Resultsmentioning
confidence: 99%
“…Drugs currently used in clinical practice are reported in the following studies: midazolam was investigated in 33 trials [7, 1416, 19, 27, 28, 31, 33, 35, 39–45, 47, 48, 5054, 59, 61, 63, 66–71], nitrous oxide in seven [26, 30, 34, 42, 46, 50, 51], ketamine in eight [13–17, 26, 34, 37, 44, 49, 70], dexmedetomidine in one [49] and propofol in four [13, 14, 46, 47]. Besides, all drugs investigated in 23 studies were the ones currently used: 19 involved midazolam [7, 19, 27, 31, 33, 35, 40, 41, 5052, 54, 61, 63, 66–70], three nitrous oxide [46, 50, 51], four ketamine [13, 17, 49, 70], one dexmedetomidine [49] and two propofol [13,46]. …”
Section: Resultsmentioning
confidence: 99%
“…the Stroop task) might have been compromised if the explicit cognitions measure (i.e. the ACQNow) preceded it (see Stewart, Buffett-Jerrott, Finley, Wright, & Valois Gomez, 2006), thus we presented the Stroop task prior to the post-MMIP ACQ-Now. However, it is possible that the Stroop task might have differentially impacted the effects of the MMIPs (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…1,3,6,[8][9][10][12][13][14][15][16][17] Multiple investigators have reported transient cognitive impairment after administration of midazolam in different clinical settings, including gastrointestinal endoscopy, 1,12,13,17 pediatric anesthesia, 6,14-16 and outpatient OMS. 3,10,11 However, most of these studies used various psychomotor assessments as their primary outcome measurement and did not specifically assess recovery room LOS, as was performed in the present study.…”
Section: Discussionmentioning
confidence: 99%